Determinantes do sucesso de campanhas de equity e de reward crowdfunding - Felipe, Israel José dos Santos (2017)
In recent years, the advancement of financial technologies, 'Fintechs', has profoundly modified the way of doing business in several countries. A good example of this is the crowdfunding market, which has benefited from the 'wisdom of the crowds' to enable individuals and small businesses to raise funds necessary for the development of their business. Barriers access to finance, especially collections of consolidated financial information and business-related collateral, have limited the use of financial resources to a broad range of ventures. As a result, crowdfunding has attracted the attention of a large part of the finance and entrepreneurship communities, which point to a vast economic, financial and innovative potential for this modality of financing. However, some studies have reported that crowdfunding may be sensitive to information asymmetry, similar to what occurs with traditional funding channels. Therefore, this research intends to investigate the process of capital allocation in the crowdfunding market, based on approaches that can provide information capable of smoothing the informational friction in the collective funding process. The first approach is the use of semantic analysis of mass media news, which can be applied on the behavior of investors and thus reveal information that serves as a parameter for choosing the best timing for the investment decision and for strategies reduction of business exposure to factors external to the financing process. The second approach consists of the geography of investments, that is, the observation of the geographical characteristics of the origins of the contributions made in the enterprises. Thus, economic and demographic information can be used to select the location of the projects, as well as the geographical orientation of the financing campaign. To fulfill the objective of this research, four trials were developed. The first essay points out a current research agenda around crowdfunding and presents theoretical and empirical discussions on this topic. The second essay identifies the determinants of the success of funding for reward crowdfunding projects, through consideration of headquarters and project attributes. Based on more than 4,200 projects from 417 Brazilian cities, the main results obtained through logit regression and survival analysis suggest that art projects, those that intend larger sums of resources, and those that offer a greater number of rewards are, probably, less successful. On the other hand, projects accounting for more support and those developed in regions with a higher concentration of per capita household income tend to be more successful in their financing campaigns. The third essay investigates the effect of the geographical characteristics of the origin of the contributions and the textual sentiment of the news about the capture of reward crowdfunding. Based on more than 350,000 contribution operations, allocated in more than 2,600 crowdfunding projects, based in 390 Brazilian cities, the research findings indicate that the operational attributes of the projects may lead to increases in the value of the contributions. With respect to geography, the distance between entrepreneur / investor can reduce the tendency of the investor to deposit larger amounts in the ventures. However, the concentration of household income per capita has shown that regions with higher income stocks can contribute more to collective initiatives. Both pessimistic and optimistic news could influence the behavior of contributions in ventures. That is, through a pessimistic scenario, investors tend to deposit smaller amounts in the ventures. On the other hand, in optimistic scenarios, they are inclined to make bigger investments. Finally, the fourth essay analyzes the value of equity investments in equity crowdfunding ventures, through semantic analysis of the media and the geography of financial contributions. Based on 736 investments made in 22 equity crowdfunding ventures located in nine Brazilian cities, the results of the study indicate that the attributes of the ventures may impact the value of the capital allocation. As far as investor behavior on the news is concerned, it is noted that mass news releases with a greater number of positive words can encourage investors to apply larger financial amounts in the ventures. In contrast, the geographical distance between entrepreneur-investor may negatively affect the value of these investments. It is hoped that the empirical results presented here can provide theoretical contributions and managerial implications for academia, professionals, platform managers and public policymakers.